2017
DOI: 10.2135/cropsci2016.09.0812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Amino‐Acid‐Based Fertilizer for Grow‐In of Creeping Bentgrass Putting Greens

Abstract: Turfgrass grow‐in on sand‐based putting greens usually incurs a high risk for nitrogen (N) leakage. Our objective was to evaluate how substitution of a standard mineral fertilizer with an amino‐acid‐based fertilizer affects creeping bentgrass (Agrostis stolonifera L.) establishment rate and the concentration of nitrate and total N in drainage water. The experiment was conducted from 19 May to 26 July 2016 in the United States Golf Association green field lysimeter facility at Landvik, Norway. The liquid fertil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…The lack of shoot weight increase could be due to some sort of plant growth regulating (PGR) function. In previous work, amino acid applications have been reported to affect endogenous plant hormone levels (Aamlid et al., 2017; Carbonera et al., 1989; Jones & Christians, 2011; Merewitz et al., 2012; Zhang et al., 2013), which demonstrates how amino acid applications can result in PGR activity.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…The lack of shoot weight increase could be due to some sort of plant growth regulating (PGR) function. In previous work, amino acid applications have been reported to affect endogenous plant hormone levels (Aamlid et al., 2017; Carbonera et al., 1989; Jones & Christians, 2011; Merewitz et al., 2012; Zhang et al., 2013), which demonstrates how amino acid applications can result in PGR activity.…”
Section: Resultsmentioning
confidence: 83%
“…The lack of shoot weight increase could be due to some sort of plant growth regulating (PGR) function. In previous work, amino acid applications have been reported to affect endogenous plant hormone levels (Aamlid et al, 2017; a Due to a non-significant interaction between treatment and runs, results have been combined across runs and are presented as a single dataset.…”
Section: Plant Biomassmentioning
confidence: 99%
“…Given the limited water holding capacity of the root zone and the high temperature and low natural precipitation in May, June and especially July 2014, it was not expected that irrigation only once a week, albeit to FC, would be sufficient to produce a visual quality scores close to 7 on the commonly used scale from 1 to 9. Earlier research on the same green suggested that creeping bentgrass is one of the more sensitive turfgrass species to drought stress (Aamlid, Knox et al, 2016) and that an increase in irrigation frequency from once to twice per week is likely to improve turf quality during the peak summer period (Aamlid, Riley et al, 2016). Possible reasons for the good results with FC1 irrigation in the early summer of 2014 may have been that the creeping bentgrass was younger (seeded 2013) than in our previous trials, and that it was gradually conditioned to tolerate warmer and drier conditions as the temperature increased and the natural rainfall decreased from May to July (Jordan et al., 2003; Fu & Dernoeden, 2009; Kamran et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Glycine betaine treatments were useful for salt tolerance stress enhancement also on perennial ryegrass cultivated in plastic cups mowed at 6 cm [28]. In field plots, a faster grow-in on creeping bentgrass (Agrostis stolonifera L.) was observed when receiving amino acid based biostimulants than on plots receiving mineral fertilizers [29]. In a C3 mixed lawn, a low rate of an amino acid product enhanced turfgrass aesthetics, as a positive effect reducing disease incidence was observed [30].…”
Section: Introductionmentioning
confidence: 99%